Noninvasive detection of enzyme activity in tumor models of human ovarian cancer using catalyCEST MRI. Issue 5 (25th May 2016) - Sinharay, Sanhita; Randtke, Edward A.; Jones, Kyle M.; Howison, Christine M.; Chambers, Setsuko K.; Kobayashi, Hisataka; Pagel, Mark D.
Abstract : Purpose: We proposed to detect the in vivo enzyme activity of γ‐glutamyl transferase (GGT) within mouse models of human ovarian cancers using catalyCEST MRI with a diamagnetic CEST agent. Methods: A CEST‐FISP MRI protocol and a diamagnetic CEST agent were developed to detect GGT enzyme activity in biochemical solution. A quantitative Michaelis‐Menten enzyme kinetics study was performed to confirm that catalyCEST MRI can measure enzyme activity. In vivo catalyCEST MRI studies generated pixel‐wise activity maps of GGT activities. Ex vivo fluorescence imaging was performed for validation. Results: CatalyCEST MRI selectively detected two CEST signals from a single CEST agent, whereby one CEST signal was responsive to GGT enzyme activity and the other CEST signal was an unresponsive control signal. The comparison of these CEST signals facilitated in vivo catalyCEST MRI studies that detected high GGT activity in OVCAR‐8 tumors, low GGT activity in OVCAR‐3 tumors, and low or no GGT activity in muscle tissues. Conclusion: CatalyCEST MRI with a diamagnetic CEST agent can detect the level of GGT enzyme activity within in vivo tumor models of human ovarian cancers. Magn Reson Med 77:2005–2014, 2017. © 2016 International Society for Magnetic Resonance in Medicine